2011
DOI: 10.1038/hr.2011.135
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of visit-to-visit and ambulatory blood pressure variability to vascular function in African Americans

Abstract: BACKGROUND Visit-to-visit clinic blood pressure variability (BPV) and 24-hour BPV have both been identified as independent risk factors for cardiovascular (CV) morbidity and mortality; however the mechanisms contributing to the increased CV risk as yet are unclear. The purpose of this study was to assess the relationship between BPV and endothelial function in a cohort of putatively healthy African Americans. METHODS 36 African Americans who were sedentary, non-diabetic, non-smoking, free of cardiovascular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
109
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(112 citation statements)
references
References 36 publications
3
109
0
Order By: Relevance
“…It is therefore generally thought that NMD depends mainly on nitroglycerin-induced smooth muscle function, and that the contribution of endothelial function is almost negligible. In a study of 36 African Americans, Diaz et al 13 showed that higher visit-to-visit BPV (SD SBP and CV SBP) was associated with a lower FMD/NMD ratio, independent of age, body mass index and mean BP levels. Our finding of a significant negative association between visitto-visit BPV and FMD (Table 4) in Japanese patients was in accordance with their study, although this is the first report to show an association between visit-to-visit BPV and endothelial dysfunction in CKD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore generally thought that NMD depends mainly on nitroglycerin-induced smooth muscle function, and that the contribution of endothelial function is almost negligible. In a study of 36 African Americans, Diaz et al 13 showed that higher visit-to-visit BPV (SD SBP and CV SBP) was associated with a lower FMD/NMD ratio, independent of age, body mass index and mean BP levels. Our finding of a significant negative association between visitto-visit BPV and FMD (Table 4) in Japanese patients was in accordance with their study, although this is the first report to show an association between visit-to-visit BPV and endothelial dysfunction in CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…10 Endothelial dysfunction is considered to be the initial pathogenic event of atherosclerosis and is a risk factor for cardiovascular disease. 11,12 Keith et al 13 showed that higher visit-tovisit BPV was associated with endothelial dysfunction in African Americans, and suggested that endothelial dysfunction may be the link between visit-to-visit BPV and atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the results obtained in this paper, Diaz et al 7 suggest that blood pressure variance is a more important predictor of cardiovascular diseases than office or home blood pressure, although their cross-sectional study shows only the relationship between vascular function and blood pressure variance and does not show a direct cause-and-effect relation between high blood pressure and cardiovascular events. Additionally, in this study, a single 0.4 mg dose of a sublingual nitroglycerin tablet was given to assess NMD, an endothelium-independent vasodilation measure.…”
mentioning
confidence: 61%
“…Guyton described how this latter factor contributes the most to controlling blood pressure after the arterial pressure suddenly becomes abnormal. 6 In this issue of the Journal, Diaz et al 7 estimated blood pressure, including visit-to visit and ambulatory blood pressure variability, office blood pressure and 24-hour blood pressure, in nonmedicated African Americans after a low-fat, low-salt diet and compared the values with flow-mediated vasodilation (FMD), nitroglycerin-mediated dilatation (NMD) and their ratio. They concluded that an increase in blood pressure variation, such as visit-to-visit systolic blood pressure variability, 24-hour systolic blood pressure variability and 24-hour diastolic blood pressure variability, is associated with reduced endothelial function as well as reduced vascular smooth muscle function.…”
mentioning
confidence: 99%
See 1 more Smart Citation